2019
DOI: 10.1177/2056305119865465
|View full text |Cite
|
Sign up to set email alerts
|

Examining Emergent Communities and Social Bots Within the Polarized Online Vaccination Debate in Twitter

Abstract: Many states in the United States allow a “belief exemption” for measles, mumps, and rubella (MMR) vaccines. People’s opinion on whether or not to take the vaccine can have direct consequences in public health. Social media has been one of the dominant communication channels for people to express their opinions of vaccination. Despite governmental organizations’ efforts of disseminating information of vaccination benefits, anti-vaccine sentiment is still gaining momentum. Studies have shown that bots on social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 48 publications
(62 reference statements)
9
118
0
1
Order By: Relevance
“…19,34 Content appears to transfer between users who share similar sentiments regarding vaccination but rarely across those with differing opinions, suggesting the structure of such platforms may give the illusion of debate, but in practice mainly serves to reinforce previously-held opinions rather than the consideration of new ones. 40 Such ideologic isolation may limit public health penetration to promote vaccination on social media. 40 More recently, the rapid spread of COVID-19 and resultant global pandemic have become a focus of intense social media discourse, with Twitter reporting a COVID-19 related tweet every 45 milliseconds and the hashtag #coronavirus rapidly becoming the 2 nd most used in 2020.…”
Section: Vaccine Content On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…19,34 Content appears to transfer between users who share similar sentiments regarding vaccination but rarely across those with differing opinions, suggesting the structure of such platforms may give the illusion of debate, but in practice mainly serves to reinforce previously-held opinions rather than the consideration of new ones. 40 Such ideologic isolation may limit public health penetration to promote vaccination on social media. 40 More recently, the rapid spread of COVID-19 and resultant global pandemic have become a focus of intense social media discourse, with Twitter reporting a COVID-19 related tweet every 45 milliseconds and the hashtag #coronavirus rapidly becoming the 2 nd most used in 2020.…”
Section: Vaccine Content On Social Mediamentioning
confidence: 99%
“…40 Such ideologic isolation may limit public health penetration to promote vaccination on social media. 40 More recently, the rapid spread of COVID-19 and resultant global pandemic have become a focus of intense social media discourse, with Twitter reporting a COVID-19 related tweet every 45 milliseconds and the hashtag #coronavirus rapidly becoming the 2 nd most used in 2020. 41,42 Unfortunately, false and misleading information about COVID-19, potentially dangerous treatments, and eventual vaccination continues to grow on social media platforms.…”
Section: Vaccine Content On Social Mediamentioning
confidence: 99%
“…Although so-called "anti-vaxxers" are a minority of the population, they are a vocal and growing community on social media platforms like Twitter [28]. The communities that form around these sentiments also tend to be "highly clustered" [66], engaging with one another, but not with other networks of users [28]. They are also vulnerable to misinformation, which spreads easily on social media [6], and is most rampant among the overconfident -that is, those who think they know more than experts [39].…”
Section: Introductionmentioning
confidence: 99%
“…A network analysis method has been used to observe antivaccination movements on social media. Yuan et al [ 61 ] analyzed the retweet network related to the MMR vaccine; they discovered that users with pro- and antivaccine views retweet much more from their own opinion communities. Himelboim et al [ 62 ] also found subgroups regarding the HPV vaccine conversation on Twitter, noting that interactions and information flows mainly occurred inside each subgroup.…”
Section: Related Workmentioning
confidence: 99%